2018
DOI: 10.1007/s40093-018-0198-6
|View full text |Cite
|
Sign up to set email alerts
|

Malting barley response to integrated organic and mineral nutrient sources in Nitisol

Abstract: Purpose Depletion of soil fertility accounts for the low yield and quality of malting barley (Hordeum vulgare) in Ethiopia. Mineral fertilizers can counteract nutrient depletion but are unaffordable by low-input farmers. Organic amendments can contribute to correct soil degradation but are often unavailable in the required amounts. Therefore, this experiment was conducted to investigate the effects of combined use of organic and mineral amendments on the yield and quality of malting barley, and on selected soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Similar results were also reported on barley (Agegnehu et al 2016;Assefa 2015), wheat (Demelash et al 2014;Getachew et al 2014), tef (Getachew et al 2014), maize (Mahmood et al 2017;Wakene et al 2005), Okra (Afe and Oluleye 2017) and tomato (Rajaie and Tavakoly 2016). This phenomenon may be attributed to positive changes of soil characteristics and nutrients availability (Tadesse et al, 2018).…”
Section: Growth and Yieldsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar results were also reported on barley (Agegnehu et al 2016;Assefa 2015), wheat (Demelash et al 2014;Getachew et al 2014), tef (Getachew et al 2014), maize (Mahmood et al 2017;Wakene et al 2005), Okra (Afe and Oluleye 2017) and tomato (Rajaie and Tavakoly 2016). This phenomenon may be attributed to positive changes of soil characteristics and nutrients availability (Tadesse et al, 2018).…”
Section: Growth and Yieldsupporting
confidence: 70%
“…In addition, Tadesse et al, (2018) stated that integrated management of organic and mineral fertilizers achieved high yield of barley and enhanced grain quality and soil fertility. This is recommended for sustainable malting barley production.…”
Section: Growth and Yieldmentioning
confidence: 99%
“…In addition to that it improves water holding capacity of soil which is of immense importance under declining water sources. Therefore, improvement in plant height, yield and yield parameters of cotton plant might be the result of availability of ideal rhizospehre conditions owing to incorporation of FYM that affect rhizospehre microbial activity and improve mobilization of soil adhered nutrients (Muneshwer et al, 2001;Nevens and Reheul, 2003;Getachew et al, 2016;Kassu et al, 2018). Performance of plants is improved by the presence/activity of microbes including mycorrhizal fungi or nitrogen fixing symbiotic bacteria ( Jacoby et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Getachew Agegnehu et al (2016); Assefa Workineh (2015) revealed that integrated use of organic and inorganic fertilizers resulted in yield benefits greater than using them alone. The improved yields of barley due to combined application of organic and mineral amendments resulted from positive changes to the soil, including increased soil pH, available P and total N, and possibly other macro-and micronutrients (Kassu Tadesse et al, 2018).…”
Section: Integrated Effect Of Organic and Inorganic Fertilizers On Fomentioning
confidence: 99%